2018
DOI: 10.1002/suco.201700253
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional FEM loading stress analysis on a new airport concrete pavement ultra‐thin whitetopping overlay structure

Abstract: In order to solve capability problems occurred in airport pavement slabs, a new airport concrete pavement ultra‐thin whitetopping (UTW) overlay structure was put forward on the basis of UTW theory. By modeling the structure in the FEM software ANSYS and applying loads on it, the structural critical loading position was determined, stress variation pattern at the bottom of the overlay slab was studied regarding the changes in overlay slabs' size and thickness as well as the bonding conditions between the asphal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The accuracy and reliability of the HWD was the subject of simulation and analysis by the model, and the results were consistent with the model simulation [10]. Zhu Maojiang constructed a three-dimensional finite element model based on the UTW theory to study the variation in the dimensional thickness of the paving slab and the tensile stress at the bottom of the slab, and proposed quality control criteria for asphalt paving and UTW paving, including the dimensions and thickness of the paving slab and the modulus of elasticity of the material [11]. Prawesti concluded that the performance of the existing airport pavement was no longer compatible with the development of transport technology.…”
Section: Introductionsupporting
confidence: 59%
“…The accuracy and reliability of the HWD was the subject of simulation and analysis by the model, and the results were consistent with the model simulation [10]. Zhu Maojiang constructed a three-dimensional finite element model based on the UTW theory to study the variation in the dimensional thickness of the paving slab and the tensile stress at the bottom of the slab, and proposed quality control criteria for asphalt paving and UTW paving, including the dimensions and thickness of the paving slab and the modulus of elasticity of the material [11]. Prawesti concluded that the performance of the existing airport pavement was no longer compatible with the development of transport technology.…”
Section: Introductionsupporting
confidence: 59%
“…In this case, existing emergency repair and construction materials can no longer fully cope with new repair needs, and novel emergency repair materials and construction methods are in urgent need. [58][59][60][61][62] Considering that CC can be tailored at will into different shapes before hardening and that a coil of CC can provide a sufficiently long pavement distance, CC perfectly suits the emergency repair demands of airport and airdrome pavement. However, before using CC for the emergency repair and construction of airport pavements, two questions must be answered: (1) how can the compressive strength, flexural strength, and wear resistance of CC be improved; (2) how can the bond performance with the base course be enhanced.…”
Section: Emergency Repair and Construction Of Airport Pavementsmentioning
confidence: 99%
“…Literature [3] through multiple comparative experiments, collect data for reference, comparison and analysis to determine the influence of RCA graduation, RCA admixture, fly ash admixture and water/cement ratio (w/c) on RCA, the results of the study show that the degree of influence on the RAC in the order of w/c > RCA content > RCA gradation > fly ash admixture. Literature [4] proposes a new type of ultra-thin white top (UTW) overlay structure for airport concrete pavements based on UTW Liliana. Modeling, simulation and analysis are carried out, and the results show that the size and thickness of the UTW overlay should be strictly controlled to reduce the tensile stress on the surface of the overlay and the life of the pavement structure.…”
Section: Introductionmentioning
confidence: 99%